2015
DOI: 10.9755/ejfa.2015-04-018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abiotic Factors on Cell Biomass and Rosmarinic Acid Production in Cell Suspension Cultures of Orthosiphon stamineus Benth

Abstract: Orthosiphon stamineus Benth. is a medicinal plant belongs to Lamiaceae family. Due to the high variations in rosmarinic acid produced from the fi eld-derived plants, cell suspension culture techniques was previously suggested and practiced as the alternative for cell biomass and rosmarinic acid (RA) production. In the present study, the effects of medium pH, photoperiod, temperature and sucrose were evaluated on cell biomass and rosmarinic acid production using three different cell lines of O. stamineus. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The Murashige and Skoog media, known as MS, contain 40 mM nitrogen in NO3and 29 mM NH4 + . Several previous studies reported callus induction in a variety of O. aristatus on MS base media with several growth regulating compositions including MS + NAA 1 mg/L + 2,4-D 1 mg/L (Bordbar et al 2015); MS + 1.0 mg/L Kinetin + 1.0 mg/L IAA and MS + 2 mg/L 2,4-D (Ali et al 2017). This study provides new information about the optimum concentration of growth regulators in growing two callus varieties of cats.…”
Section: Callus Inductionmentioning
confidence: 99%
“…The Murashige and Skoog media, known as MS, contain 40 mM nitrogen in NO3and 29 mM NH4 + . Several previous studies reported callus induction in a variety of O. aristatus on MS base media with several growth regulating compositions including MS + NAA 1 mg/L + 2,4-D 1 mg/L (Bordbar et al 2015); MS + 1.0 mg/L Kinetin + 1.0 mg/L IAA and MS + 2 mg/L 2,4-D (Ali et al 2017). This study provides new information about the optimum concentration of growth regulators in growing two callus varieties of cats.…”
Section: Callus Inductionmentioning
confidence: 99%
“…They explained that this could be due to light exposure influencing the lower expression rate of key enzymes for the biosynthesis of gibberellins, resulting in lower growth rates in the cultures. Besides, illumination had also no significant effect on the growth and cell biomass accumulation on cell suspension cultures in Angelica sinensis (Zhang et al, 2019) and Orthosiphon stamineus (Bordbar et al, 2015). This was not the case for the cells of C. nutans as the light was observed to be an important factor for cell growth in liquid media.…”
Section: Effect Of Light Illumination On Cell Biomass Productionmentioning
confidence: 90%
“…This includes the selection of highyielding cell cultures and the manipulation of chemical or physical factors to improve the growth of cell biomass and to stimulate the biosynthesis of secondary metabolites (Murthy et al, 2014). The accumulation of cell biomass via the in vitro system has been reported to be influenced by various factors such as plant growth regulators, light, and temperature (Bordbar et al, 2015;Georgieva et al, 2015). Light illumination is one of the key factors in cell cultures particularly to provide energy for the metabolism of the cultured cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is necessary to produce active compounds without directly processing them from the original plant and efforts to micropropagate O. aristatus using plant tissue culture technique. Several studies on tissue culture of O. aristatus have previously been reported, including induction of the callus from O. aristatus, which can grow on MS medium with 0.4 ppm 2,4-D;1 ppm NAA + 1 ppm 2,4-D; 2 ppm 2, 4-D; 1.0 ppm Kinetin + IAA 1.0 ppm (Faramayuda et al, 2020;Wai and Lai, 2004;Bordbar et al, 2015;Sheena and Jothi, 2015;Ali et al, 2017;Faramayuda et al, 2021a). However, these studies did not report identification of active compounds in the callus of the O. aristatus, which were derived using Gamborg, Schenk, and Hildebrandt (SH) and N6 media.…”
Section: Research Articlementioning
confidence: 99%